STRATEGI VISUALISASI PRODUK UNTUK UMKM NAIK KELAS: PELATIHAN FOTO PRODUK DAN PACKAGING PADA KELOMPOK PEMBERDAYAAN PEREMPUAN DESA BENDOSARI - Sabda Aji Kurniawan; Martha Racwel Patty; Indari Umayah (Universitas Muhammadiyah Ponorogo, 2026)
This community service program (PKM) aims to enhance the competitiveness of women-led MSMEs in Bendosari Village through visual strategies focusing on product photography and packaging design. The program was implemented using a participatory approach through three main stages: preparation, implementation, and evaluation. During the preparation stage, the PKM team collaborated with local partners to develop training materials on product photography using smartphones and packaging design with Canva, a user-friendly graphic design application. The implementation stage consisted of two sessions: the first (March 18, 2025) delivered hybrid-based socialization and basic training, while the second (March 25, 2025) focused on hands-on workshops. Participants completed a pre-test prior to training and underwent evaluations at the end of the program. The results indicate significant improvements, with participants’ understanding of the importance of product photos rising from 55% to 86%, photography skills from 48% to 85%, technical abilities in lighting and background setup from 45% to 76%, packaging design skills from 50% to 78%, and self-confidence from 52% to 88%. These findings confirm that practice-oriented methods, interactive discussions, and product-based evaluations effectively improve knowledge, technical skills, and confidence among MSME actors. Furthermore, the program provides opportunities for future development through continued assistance in digital marketing to ensure long-term sustainability and competitiveness.